Robot Path Planning using Particle Swarm Optimization of Ferguson Splines - Saska, M.; Macas, M.; Preucil, L.; Lhotska, L. (2006 IEEE Conference on Emerging Technologies and Factory Automation, 2006)
Robot path planning problem is one of most important task mobile robots. This paper proposes an original approach using a path description by string of cubic splines. Such path is easy executable and natural for car-like robot. Furthermore, it is possible to ensure smooth derivation in connections of particular splines. In this case, the path planning is equivalent to optimization of parameters of splines. An evolutionary technique called particle swarm optimization (PSO) was used hereunder due to its relatively fast convergence and global search character. Various settings of PSO parameters were tested and the best setting was compared to two classical mobile robot path planning algorithms.